THE STATE OF SLOVENIAN AGRO-FOOD SECTOR AFTER ACCESSION TO THE EU - Volk, Tina; Rednak, Miroslav; Erjavec, Emil (Economics of Agriculture, 2007)
The paper describes and analyzes the changes in Slovenian agro-food sector in the period 1992-2006 with more emphasis on the years after 2000 in the light of accession to the European Union (EU). The accession has not caused any major difficulties in the Slovenian agriculture as a whole. Such an outcome can be attributed to the fact that the objectives and mechanisms of Slovenian agricultural policy were gradually brought into line with the Common Agricultural Policy (CAP) already in the pre-accession period. Therefore, the adoption of the CAP on accession largely meant a continuation of the measures pursued under the national agricultural policy, but with higher funds for the agricultural support. The agricultural income remained at the relatively high level compared with the previous years and the analyses of the main factors determining income revealed the continuation of trends typical for the period after 1999 – a slightly upward trend in the agricultural output volume, a downward trend in the producer prices of agricultural products and an intensive upward trend in the subsidies for farmers. The most evident changes that could be attributed directly to the EU accession may be observed in the agro-food trade. Slovenia is traditionally a net food importer. However, abolishing customs protection on the imports from the EU and a rise in the customs duties levied on the exports to the third countries after the accession has increased the trade deficit to the highest level so far. Trade was somewhat reoriented from other countries to EU Member States, especially on the export side. Opening up the market after the accession increased a competitive pressure on the food industry and the business performance of the sector deteriorated significantly. The Slovenian agro-food chain is faced with some important challenges. The problem of relatively poor competitiveness of the sector has not yet been solved, and comprehensive structural changes and adjustments are still needed.